Making Senegal a Hub for West Africa : Reforming the State, Building to the Future - Kireyev, Alexei; Mansoor, Ali. (Washington, D.C. : International Monetary Fund, 2015)
This Departmental Paper takes stock of Senegal's achievements in the past few years under IMF-supported programs and identifies key reform pillars for the future. IMF staff analyses Senegal's new development strategy, Plan Senegal Emergent, which aims to make Senegal an emerging market economy by 2035.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet